Development of Nateh Village Tourism Potential and Digitizing Promotion Using Augmented Reality, Websites and Community Based Tourism - Agusta, Akhmad Riandy; Suriansyah, Ahmad; Pratiwi, Diani Ayu; Noorhapizah; Sari, Raihanah; Jannah, Fathul (Indonesian Journal of Community Services Cel, 2022)
Problems in the management of tourism in Nateh Village. The main obstacle is the management of the tourism potential of this village is that there is no tourism manager, the village community is less participative in developing the tourism potential of Nateh Village, there are no digital tourism promotion efforts, such as websites or applications that can increase tourist interest in visiting Nateh Village. In addition, tourism is also poorly managed and promoted. This community service activity aims to produce a Nateh Village tourism management group, produce a Nateh Village tour package design, produce an augmented reality design for Nateh Village, and produce a Nateh Village tourism website that can be used to promote tourism potential in Nateh Village. The method used consists of observation, empowering tourism management communities, training to develop tour package offers, training on making augmented reality, training on managing websites, training on digitizing tour package offers, socializing the use of websites and applications, and evaluating activities. The results of this community service activity have provided a Nateh Village tourism management group, a Nateh Village tour package design is available which is included in the website, an augmented reality design for Nateh Village is available and a Nateh Village tourism website is available which can be used to promote tourism potential in Nateh Village. 4 tourism potentials and 5 tour packages have been produced which are promoted through the website and augmented reality.